Evaluation of Fruit Characters, Xanthones Content, and Antioxidant Properties of Various Qualities of Mangosteens (Garcinia mangostana L.) - Ani Kurniawati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
Xanthone in mangosteen fruit hull has antioxidant activities. The objective of this experiment was to determine xanthones content, physical and chemical characters, and antioxidant potentials of several groups of mangosteens qualities. The experiment was carried out from January 2008 to August 2008. The research used a randomized complete block design with four replications. The treatments were four physical fruit conditions: large size mangosteens (≥ 100 g), small size mangosteens (min. 50 g), yellow sap dotted fruits, and scabbed fruit. The parameters being observed were physical and chemical characteristics, xanthone content, and radical scavenging activity of mangosteen fruit hull extract. The results demonstrated that the physical condition of fruit significantly affected physical fruit hull characters and chemical fruit characters. Characters of fruit hull, thickness, fresh weight, and dry weight, differed among fruit qualities. The physical condition of fruit hull also significantly influenced total soluble solid and vitamin C content, but did not affect total titrable acid and degree of acidity of the fruits. Fruit hulls of all groups of mangosteen qualities had similar antioxidant properties with the IC50 value of 5.57-6.11 ppm. Keywords: benzophenone, scab, vitamin C, yellow sap